Trend Research of City Center Public Open Space Transformation: A Systematic Literature Review - Pramono, Retno Widodo Dwi (Department of Urban and Regional Planning, Universitas Diponegoro, 2025)
The transformation of city centers is crucial for enhancing sustainability and livability, as urban environments face increasing challenges from rapid urbanization and environmental degradation. As urban areas continue to expand and evolve, the need for sustainable practices becomes increasingly urgent. The city center, often the heart of urban life, plays a pivotal role in shaping social interactions, economic activities, and environmental impacts. The transformation of city center and their public open spaces is a multifaceted process that requires careful consideration of design, community engagement, and accessibility. By prioritizing these elements, urban planners and policymakers can create vibrant, inclusive, and sustainable urban environments that enhance the quality of life for all residents. This research aims to see Research Trends and Future Direction using the method of A systematic Literature reviews with databases derived from Scopus and WOS (Web of Science) and in data management and data analysis using Bibliometrix, R-Studio and Biblioshiny applications. This research looks at reviews several documents related to the most productive authors and the most cited articles. In addition, it also looks at topic trends, theme mapping and method research formed to see trends in research topics and future research. After processing the data, the results obtained that “Public Space” is most keyword used and is also still an opportunity in research. In addition, the themes of City Center, Tourism and Urban Regeneration are future themes that need to be discussed more in the city center public open space transformation.